2018
DOI: 10.1371/journal.pone.0193323
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor and VEGF pathways for gene-blood lead interactions, on bone mineral density, in Korean smokers

Abstract: Osteoporosis has a complex etiology and is considered a multifactorial polygenic disease, in which genetic determinants are modulated by hormonal, lifestyle, environmental, and nutritional factors. Therefore, investigating these multiple factors, and the interactions between them, might lead to a better understanding of osteoporosis pathogenesis, and possible therapeutic interventions. The objective of this study was to identify the relationship between three blood metals (Pb, Cd, and Al), in smoking and nonsm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Quality control procedures were adopted, such as missing genotype frequency > 0.5% and minor allele frequency (MAF) ≤ 0.05. After sample and genotype quality controls, 344,396 SNPs for 3180 individuals were available in the KARE database [ 26 , 27 ]. The KARE data used to support the findings of this study are restricted by the Institutional Review Board of the Korean National Institute of Health, who can contact at National Biobank of Korea ( http://koreabiobank.re.kr , 82–1661-9070).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality control procedures were adopted, such as missing genotype frequency > 0.5% and minor allele frequency (MAF) ≤ 0.05. After sample and genotype quality controls, 344,396 SNPs for 3180 individuals were available in the KARE database [ 26 , 27 ]. The KARE data used to support the findings of this study are restricted by the Institutional Review Board of the Korean National Institute of Health, who can contact at National Biobank of Korea ( http://koreabiobank.re.kr , 82–1661-9070).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, 344,396 SNPs were mapped to genes within 20 kb boundaries. Pathways consisting of <20 or >200 genes were excluded from further analysis, to reduce the multiple testing issue and avoid testing overly narrow or broad functional categories [ 22 , 27 ]. A false discovery rate (FDR) was used for multiple testing correction, with q values < 0.05 considered significant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, nucleotide changes on ALFY were identified in patients with microcephaly [ 94 ], as well as in oropharynx cancer [ 95 ]. WIPI4 pathogenic SNPs have been shown to cause neurological disorders, such as neurodegeneration with brain iron accumulation (NBIA) and Rett syndrome [ 96 , 97 , 98 ], while polymorphisms on WIPI2 and WIPI3 have been associated with osteoporosis [ 99 ] and a neurodevelopmental syndrome [ 100 ]. Two variants of ATG2A have been linked with both granuloma formation in Crohn’s disease and hyperuricemia [ 101 , 102 ].…”
Section: Relevant Variants On Autophagy-related Genesmentioning
confidence: 99%
“…Further, Genome Wide Association Studies (GWAS)-based pathway analysis revealed significant upregulation of nuclear receptor and VEGF pathways by body lead burden, with regard to the prevalence of osteoporosis in smokers. Their study findings highlight the probable interactions that intracellular pathways of angiogenesis and nuclear hormone signalling may play between exposure to lead and genetic variation, especially in individuals with diminished bone mineral density [3].…”
mentioning
confidence: 99%